Education for balanced development in integrated primary school - Mielczarek, Artur W. (Studia Ecologiae et Bioethicae, 2008)
The importance of education for balanced development in integrated primary school is really vital. School is one of the institutions which must supply its students with certain knowledge about the natural environment, teach them responsibility towards the natural environment and themeselves, make them aware of the dangers created by modern civilization and teach, how to use the natural resources in proper way. In the year 2004 was carried out research checking the efficiency of natural science in grade I-III of primary school teaching, the material presented below shows achieved results and the influence of natural science on young students.